2008
DOI: 10.1007/s10562-008-9440-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Sulfated Silica-Doped Tin Oxides and Their High Activities in Transesterification

Abstract: A series of sulfated silica-doped tin oxides with large surface areas (113-188 m 2 /g) have been successfully prepared from hydrothermal synthesis, followed by sulfation and calcination. These samples are characterized by XRD, FT-IR, TEM, nitrogen isotherms, and TG techniques, and obtained results indicate that the samples are composed of tetragonal nanocrystalline tin oxides and amorphous silica. Very interestingly, catalytic tests show that these sulfated silica-doped tin oxides are much more active than con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…Du et al [167] prepared several sulfated silica-doped tin oxides with large surface areas by hydrothermal synthesis, followed by sulfation and calcination. Catalytic tests in the transesterification of triacetin as a model substrate with methanol showed that sulfated silica-doped tin oxides were much more active than conventional sulfated tin oxides.…”
Section: Sulfated Zirconia Catalysts Have Been Extensively Examined Imentioning
confidence: 99%
“…Du et al [167] prepared several sulfated silica-doped tin oxides with large surface areas by hydrothermal synthesis, followed by sulfation and calcination. Catalytic tests in the transesterification of triacetin as a model substrate with methanol showed that sulfated silica-doped tin oxides were much more active than conventional sulfated tin oxides.…”
Section: Sulfated Zirconia Catalysts Have Been Extensively Examined Imentioning
confidence: 99%
“…These kinds of catalysts, including sulfated zirconia [87][88][89] and sulfated tin oxides [90] have been widely used in esterification and transesterification reactions under mild conditions. Kiss et al [87] studied several solid acid catalysts (zeolites, ion-exchange resins, and mixed metal oxides) as catalysts for the esterification of dodecanoic acid with 2-ethylhexanol, 1-propanol, and methanol.…”
Section: Sulfated Zirconia Based Catalystsmentioning
confidence: 99%
“…Utilizando o mesmo método, Garcia (2006) obteve 12,6 m 2 g -1 e utilizando o método de precipitação, a área obtida foi de 89,2 m 2 g -1 . Já Du et al (2008), sintetizando a zircônia sulfatada pelo método convencional, obtiveram um valor aproximado de 75 m 2 g -1 1.…”
Section: Resultados E Discussõesunclassified